Pengaruh Variasi Jumlah Bilah Turbin Angin Sumbu Horizontal Dengan Airfoil AG 12 Terhadap Daya - Deka Rama Ligustian; Oktarina Heriyani; Dan Mugisidi (Universitas Muhammadiyah PROF. DR. HAMKA Fakultas Teknik – Program Studi Teknik Mesin, 2023)
Wind power plant is a new renewable energy, power plant that utilizes wind turbine rotation to convert wind energy into electrical energy. One of the modifications to the wind turbine that is done is to vary the number of blades. The results of variations in the number of blades are expected to increase the efficiency of wind turbines at certain speeds. In this research, we will vary the number of blades 3, 4 and 5 with an AG 12 airfoil assisted by the Q-Blade application for simulation and find out the results of calculations in graphical form. Variations are made at a minimum wind speed of 2 m/s to a maximum wind speed of 12 m/s. With a planned power coating of 500 watts assuming a turbine rotation of 400 rpm, using a horizontal axis wind turbine (TASH). With a minimum wind speed of 2 m/s, the variations in the number of blades 3, 4 and 5 have not been able to generate power because the turbine rotation factor is too fast at low wind speeds, while at a maximum wind speed of 12 m/s the power generated by the three blade variations 3, 4, and 5 are able to meet the planned power capacity of 500 watts. The highest efficiency is obtained in the variation of blade 4 with 0.453 at wind speed 8 with a power of 300.37 watts, then 0.37 in the variation of 3 blades at a speed of 7 m/s with a power of 164.28 watts, in the variation of blade 5 the highest efficiency is in the figure is 0.29 at a wind speed of 10 m/s with a power of 409.14 watts.